Depicting the Malay culture among communities in Merbok, Kedah / Syakirah Mohammed ... [et al.] - Mohammed, Syakirah; Wan Omar, Maznah; Ibrahim, Syazliyati (2018)
Malay became Malaysia's sole national language in 1967 and has been institutionalized with a modest degree of success. This study describes the evolution of the Malay culture particularly among communities in Merbok, Kedah and how religion helps to change values, thus changes the culture of the communities. The methodology adopted in this study was through the adoption of the oral history method and was found deemed appropriate for this type of study. Culture can be defined as the integrated system that related to values, beliefs, behaviors, norms, artifacts and other works of any society. In the human history, this is the culture that divides human beings or separates one community from another. Specifically, Malay culture encompassed within the definition are the universal aspects such as philosophy of life, art, literature and language, means of livelihood, food, traditional ceremony, equipment, dress, artifact, building, traditional medical treatment and Malay norms. With modernisation, the community spirit among the Malays is slowly eroding.